The reflections on scientific significance of researching the religious factor in history of the USA - Kosmach, Pavel G. (Journal of the Belarusian State University. History, 2024)
The article deals with the current trends in social and humanitarian studies, which have actualised the study of the religious aspects of modern and contemporary history. We can see a significant increase in attention to the relevant topics in the history of the USA and other Western countries. The complexity and ambiguity of the processes of secularisation, which are connected with the development of social atomisation and the cultural fragmentation of society, are emphasised. It is concluded that the study of the religious factor contributes to the discussion about the norms and values that ensure the functioning of the republican form of government in the USA and other Western countries. It is also noted that at the present stage, different belief systems are beginning to be understood as specific adaptations that promote civility and, under certain circumstances, increase the chances of survival for their own adherents. However, the final assessment of the effectiveness of these adaptations remains controversial. The data regarding the positive relationship between the level of religiosity and the level of fertility are also important. Advances in neurophysiology allow us to better understand the biological facets of religious experience. The ideal and material components of human nature and culture turn out to be more closely connected than was previously thought. A comprehensive study of the role of religion in socio-political processes seems to be an important and promising scientific topic in the humanities of the 21st century.
Keywords: religion; history of the USA; Christianity; Protestantism; secularisation